Immunohistochemical mapping of epidermal growth-factor receptors in normal human oral soft tissue - Whitcomb, S S; Eversole, L R; Lindemann, R A (Archives of oral biology, 1993)
Epidermal growth-factor receptor (EGF-r) has been identified on basilar cells of stratified squamous epithelia and skin adnexa in man. Recent studies have mapped EGF-r to various oral cells in animals; however, complete mapping of EGF-r in normal human oral mucosa has not been done. Normal tissues from eight sites in human oral mucosa were examined for their expression of EGF-r using avidin-biotin peroxidase complex with mouse anti-EGF-r monoclonal antibody. Immunoreactivity was detected in palatal gingiva, buccal gingiva, soft palate, lateral tongue, dorsal tongue and floor of the mouth. The connective tissues of the periodontal ligament and dental pulp were non-reactive. EGF is known to exist in most body fluids, particularly saliva. In normal human mucosa, EGF is localized to connective tissue subjacent to epithelium. With the receptor in the overlying epithelium, a possible epithelial-mesenchymal interaction may exist between the receptor and ligand. A paracrine mode of action may be postulated, functioning to regulate the complex biological functions of the human oral tissues.